Hydrolytic Oxidation of Cellobiose Using Catalysts Containing Noble Metals - Oleg Manaenkov; Olga Kislitsa; Ekaterina Ratkevich; Yuriy Kosivtsov; Valentin Sapunov; Valentina Matveeva (Reactions, 2022)
Studies of the processes of the hydrolytic oxidation of disaccharides are the first step towards the development of technologies for the direct conversion of plant polysaccharides, primarily cellulose, into aldonic and aldaric acids, which are widely used in chemical synthesis and various industries. In this study, heterogeneous catalysts based on a porous matrix of hypercrosslinked polystyrene (HPS) and noble metals (Pt, Au, Ru, and Pd) were proposed for the hydrolytic oxidation of cellobiose to gluconic and glucaric acids. The catalysts were characterized using low-temperature nitrogen adsorption, hydrogen chemisorption, electron microscopy, and other methods. In particular, it was shown that the Pt-containing catalyst contained, on average, six times more active centers on the surface, which made it more promising for use in this reaction. At a temperature of 145 °C, an O2 pressure of 5 bars, and a substrate/catalyst weight ratio of 4/1, the yields of gluconic and glucaric acids reached 21.6 and 63.4%, respectively. Based on the data obtained, the mathematical model of the cellobiose hydrolytic oxidation kinetics in the presence of 3% Pt/HPS MN270 was developed, and the parameter estimation was carried out. The formal description of the kinetics of cellobiose hydrolytic oxidation was obtained.